Enhancing calibration accuracy with laser interferometry for high-resolution measuring systems - Črepinšek-Lipuš, Lucija (Advances in production engineering and management, 2024)
This paper presents an analysis of the measurement capability of laser interferometry for calibrating high-resolution measuring systems, focusing on potential errors that need to be carefully controlled to ensure adequate metrological traceability. The primary scientific research focus of our National Dimensional Metrology Laboratory is the development of metrological applications for industry, with ongoing improvements in calibration procedures for measuring machines and tools. Through a review of possible error sources, an innovative approach to reducing the most significant factors is proposed. This is specifically applied to the following calibration cases: field calibration of coordinate measuring machines, and laboratory calibration of precision probes and line scales. Instrumental and environmental errors can be effectively mitigated by using periodically calibrated laser interferometers in well-controlled air conditions, ensuring an uncertainty of 0.2 µm/m. Most geometrical errors can be minimized by precise adjustments to the interferometry and positioning systems, achieving an uncertainty of 0.3 µm/m. However, errors caused by temperature differences in the material along the measuring path remain the most influential. These arise due to the high expansion coefficient of the material and some uncertainty in its properties. After several hours of temperature stabilization, using three temperature sensors along the displacement range for software compensation, temperature differences still contribute significantly to measurement uncertainty. For example, the error is 0.5 µm/min in the case of line scale calibration and 1.1 µm/m for coordinate measuring machine calibration.
Keywords: coordinate measuring machine; črtno merilo; dimensional metrology; dimenzijsko meroslovje; high resolution measurements; koordinatni merilni stroj; laser interferometry; laserska interferometrija; line scale; measurement uncertainty; merilna negotovost; meritve visoke ločljivosti; natančna sonda; precise probe